2019
DOI: 10.3390/ijms20174303
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Key Seed-Development Genes in Common Buckwheat (Fagopyrum esculentum)

Abstract: Seed development is an essential and complex process, which is involved in seed size change and various nutrients accumulation, and determines crop yield and quality. Common buckwheat (Fagopyrum esculentum Moench) is a widely cultivated minor crop with excellent economic and nutritional value in temperate zones. However, little is known about the molecular mechanisms of seed development in common buckwheat (Fagopyrum esculentum). In this study, we performed RNA-Seq to investigate the transcriptional dynamics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 63 publications
(98 reference statements)
2
13
1
Order By: Relevance
“…The enzymes involved in this process, such as for sucrose degradation and starch synthesis, are considered to be key [ 20 , 34 ]. These enzymes include SuSase (EC 2.4.1.13), AGPase (EC 2.7.7.27), StSase (EC 2.4.1.21), SBE (EC 2.4.1.18), UGPase (EC 2.7.7.9), DBE (EC 3.2.1.68), and GBSS (EC 2.4.1.242) [ 18 , 35 ]. In this study, we identified 22 differentially expressed genes that encoded enzymes associated with starch and sucrose metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzymes involved in this process, such as for sucrose degradation and starch synthesis, are considered to be key [ 20 , 34 ]. These enzymes include SuSase (EC 2.4.1.13), AGPase (EC 2.7.7.27), StSase (EC 2.4.1.21), SBE (EC 2.4.1.18), UGPase (EC 2.7.7.9), DBE (EC 3.2.1.68), and GBSS (EC 2.4.1.242) [ 18 , 35 ]. In this study, we identified 22 differentially expressed genes that encoded enzymes associated with starch and sucrose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that cytokinin is involved in regulating grain production [ 41 , 42 ]. Other plant hormones, including BR, ET, JA, and SA, also play a crucial role in seed development and grain production [ 5 , 17 , 18 , 43 , 44 , 45 ]. In this study, we observed that many differentially expressed genes were related to plant hormone biosynthesis and/or signaling pathways; these genes included PYLs (abscisic acid receptor), ABI5 (ABSCISIC ACID-INSENSITIVE 5), PP2C (probable protein phosphatase 2C), SAPKs (serine/threonine-protein kinase), SAURs (auxin-responsive protein), JAR (jasmonic acid-amido synthetase), EIN2 (ETHYLENE-INSENSITIVE 2), and TIFY ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, classical breeding treatments such as the one described in this study shed a light on the mechanisms involved in seed production of F. esculentum . Key genes involved in seed development are already recognized, and they are genes responsible for Ca 2+ signal transduction pathway, hormone signal transduction pathways, and coding transcription factors (TFs), as well as starch biosynthesis-related genes [ 17 ]. Regarding seed size, AP2 and bZIP transcription factors, BR-signal, and ABA are considered the most important regulators [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of three hub TFs from the 17 selected key genes, which were the first-layer regulators of SCW biosynthesis, were also tested in the hulls of other three normal tartary buckwheat cultivars. qRT-PCR analysis was performed as described by Li et al [ 48 ]. The tartary buckwheat actin7 gene was used as the internal control.…”
Section: Methodsmentioning
confidence: 99%